Tensile and Microscopic Properties of High-Density Polyethylene Geonet for Rainwater Scour Resistance - Liu, Luliang; Dou, Yuanming (Frontiers in Materials, 2022)
In order to study the tensile properties of high density polyethylene (HDPE) geonet for rainwater scour resistance and the micro properties of HDPE after tensile failure, a series of tensile tests on HDPE geonet were carried out by the material testing system (MTS) tensile device. In this study, a correlation has been proposed to analyze the relationship between elongation and tensile strength of geonet material. The microscopic characteristics of HDPE geonet were performed by scanning electron microscope SU8000. High density polyethylene geonet for rainwater scour resistance was evaluated based on mechanical performance and microstructure. The rainwater scour resistance properties of high density polyethylene geonet were estimated. It is determined that the geonet improved the rainwater scour resistance of the soil slope. The mechanical test results indicate that the longitudinal mechanical properties of the geonet are better than the transversal. The scanning electron microscope images of the geonet results confirm that the polyethylene polymer produces fine and neat radial cracks during the tensile process of the geonet. The findings of this work are essential for the fundamental understanding, design, and application of the geonet.